Synthesis and Characterization of Poly (Acryl Amide - Maleic Acid) Hydrogel: Adsorption Kinetics of a Malachite Green from Aqueous Solutions. Issue 1 (2018) - Jasim, Layth S.; Radhy, Nadher D.; Jamel, Hayder O.
No abstract available